Efficient transgene expression in IVF and parthenogenetic bovine embryos by intracytoplasmic injection of DNA-liposome complexes - Vichera, Gabriel Damian (2011)
Transgenic animals constitute an important tool with many biotechnological applications. Although there have been advances in this field, we propose a novel method that may greatly increase the efficiency of transgenic animal production and thereby its application. This new technique consists of intracytoplasmic injection of liposomes, in bovine oocytes and zygotes, to introduce exogenous DNA. In the first experiment, we evaluated embryo development and EGFP expression in In Vitro Fertilization (IVF) embryos injected with different concentrations of exogenous DNA-liposome complexes (0.5, 5, 50, 500 ng pCX-EGFP/μl). The highest EGFP-embryos rates were obtained using 500 ng pCX-EGFP/μl. In the second experiment, we evaluated embryo development and EGFP expression following the injection of DNA-liposome complexes into pre-fertilized oocytes and presumptive zygotes, 16 and 24 h post-fertilization. Approximately 70% of the cleaved embryos and 50% of the blastocysts expressed EGFP, when egfp-liposome was injected 16 h post-fertilization. The percentages of positive embryos for the 24-h post-fertilization and pre-fertilization groups were 30.1 and 6.3, respectively. Blastocysts that developed from injected zygotes were analysed by PCR, confirming the presence of transgene in all embryos. Finally, we examined the embryo development and EGFP expression of parthenogenetic embryos that resulted from the injection of egfp-liposome complexes into pre-activated oocytes, and 3 and 11 h post-activated oocytes. The group with the highest expression rate (48.4%) was the one injected 3 h post-activation. In summary, this study reports the efficient, reproducible and fast production of IVF and parthenogenetic embryos expressing EGFP, by the intracytoplasmic injection of liposomes to introduce the foreign DNA.